Peningkatan Literasi Lingkungan Anak Usia Dini Melalui Pembuatan Pupuk Organik di TK Islam Syahida Jember - Rini Hardiyani; Helda Jaya Puspita; Rallyanta Tarigan; Amalia Malik; Canggih Nailil Maghfiroh (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This community service activity aims to improve environmental literacy in early childhood through the practice of making organic fertilizer from eggshells at Syahida Islamic Kindergarten in Jember. Jember Regency has a high poultry egg production, resulting in large quantities of eggshell waste that has the potential to pollute the environment if not utilized. This waste contains calcium carbonate (CaCO₃) which is beneficial for plants, so it has the potential to be processed into organic fertilizer. Activities are carried out through an organic approach experiential learning. This activity directly involved children in the washing, drying, pounding, and application of eggshell powder to plants. The results demonstrated an increased understanding of organic waste sorting, recycling concepts, and the use of eggshells as fertilizer. Teachers also gained new insights into creative and easily implemented environmental-based learning methods. Overall, this activity was effective in fostering environmental awareness from an early age while supporting locally-based organic waste management.